Fluticasone furoate and vilanterol trifenatate combination therapy for the treatment of asthma. (2nd August 2016) - Gray, Emma L.; Chang, Vicky; Thomas, Paul S.
ABSTRACT: Introduction : Combination inhaled corticosteroids (ICS) and long acting β2 -adrenergic agonists (LABA) are used in a stepwise fashion for patients whose asthma is not controlled by low dose ICS alone. Adherence is one of the main issues facing clinicians in the control of asthma symptoms with currently available combination inhalers requiring twice-daily (BD) inhalation. Fluticasone furoate (FF) and vilanterol trifenatate (VI) both have prolonged retention in the lung with effects on lung function over 24-hours and as such the combination has been proposed for once-daily (OD) dosing. Areas covered : The stepwise pharmacologic approach to asthma management is addressed, followed by a detailed assessment of the literature pertaining to the efficacy, tolerability and safety of FF/VI combination therapy for the treatment of asthma. Expert commentary : Doses of 100/25µg and 200/25µg inhaled OD, have similar improvements in lung function, asthma control as well as rates of side effects to one of the currently available BD ICS/LABA combinations, fluticasone propionate and salmeterol (FP/SAL) but have not been compared with other commonly used combinations. It is hoped that OD dosage of FF/VI can improve adherence and hence asthma control in these patients, however evidence to support this has yet to become available.